2021
DOI: 10.1097/mnh.0000000000000755
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting glomerular hyperfiltration and examining the concept of high dietary protein-related nephropathy in athletes and bodybuilders

Abstract: Purpose of reviewHigh-protein diets (HPDs) are popular but their consequences for kidney health, especially among athletes and bodybuilders who typically maintain a high protein intake for a long time, have not been investigated. This review focused on recent studies of the association of HPD with long-term kidney health and the concept of high dietary protein-related nephropathy. Recent findingsSeveral long-term observational studies including large populations have reinforced the notion that HPDs are associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…There is epidemiologic evidence showing high protein diets and certain types of protein (e.g., from red meat) are associated with impaired renal function [ 94 , 95 ]. Large epidemiological studies have linked higher protein diets (generally 1.0–1.7 g/kg/day) to impaired renal function and kidney disease within the general population [ 96 ], but such epidemiologic investigation has not been done in strength trained athletes or bodybuilders.…”
Section: Potential Other Health Risks For Bodybuildersmentioning
confidence: 99%
See 1 more Smart Citation
“…There is epidemiologic evidence showing high protein diets and certain types of protein (e.g., from red meat) are associated with impaired renal function [ 94 , 95 ]. Large epidemiological studies have linked higher protein diets (generally 1.0–1.7 g/kg/day) to impaired renal function and kidney disease within the general population [ 96 ], but such epidemiologic investigation has not been done in strength trained athletes or bodybuilders.…”
Section: Potential Other Health Risks For Bodybuildersmentioning
confidence: 99%
“…The unique protein requirements for elite bodybuilders have not been studied, so it is unclear if such high protein intake is excessive or necessary for success [ 102 ]. Regardless, there is concern that these high intakes adversely affect renal health in bodybuilders [ 93 , 96 ]. A number of studies have found that prescription of a very high protein diet (3.0–4.4 g/kg body mass/day, for between 8 weeks and 1 year) does not adversely change biomarkers of kidney and liver function in healthy resistance-trained individuals [ 103 106 ].…”
Section: Potential Other Health Risks For Bodybuildersmentioning
confidence: 99%
“…There are several hypotheses to explain the decline of renal function in PKU patients. First, protein and AA load can induce long-term glomerular hyperfiltration [30][31][32]. Considering the above, one might assume that the Phe-free AAM consumption negatively affects the kidney function [27].…”
Section: Discussionmentioning
confidence: 99%
“…13 Another challenge is that half or a higher proportion of persons with advanced CKD have diabetes or suffer from obesity and metabolic syndrome, where obese sarcopenia is more likely and for which higher dietary protein intake is traditionally recommended. Higher protein intake may worsen CKD progression and uremic symptoms by increasing the level of nitrogenous endproducts of amino acids leading to higher circulating levels of uremic toxins; 11,14,15 moreover, individual disease states may benefit from distinct nutritional interventions given data supporting ketogenic diet for polycystic kidney disease, gluten-free diet for IgA nephropathy, and lower glycemic index foods for diabetic kidney disease. 12 However, engaged dietitians equipped with well-designed dietary management models can implement patient-centered MNT strategies using telenutrition and other educational and monitoring modalities.…”
mentioning
confidence: 99%